Insights into the structure and regulation of glucokinase from a novel mutation (V62M), which causes maturity-onset diabetes of the young. - Gloyn, A; Odili, S; Zelent, D; Buettger, C; Castleden, H; Steele, A; Stride, A; Shiota, C; Magnuson, M; Lorini, R; d'Annunzio, G; Stanley, C; et al. (2005)
Glucokinase (GCK) serves as the pancreatic glucose sensor. Heterozygous inactivating GCK mutations cause hyperglycemia, whereas activating mutations cause hypoglycemia. We studied the GCK V62M mutation identified in two families and co-segregating with hyperglycemia to understand how this mutation resulted in reduced function. Structural modeling locates the mutation close to five naturally occurring activating mutations in the allosteric activator site of the enzyme. Recombinant glutathionyl S-transferase-V62M GCK is paradoxically activated rather than inactivated due to a decreased S0.5 for glucose compared with wild type (4.88 versus 7.55 mM). The recently described pharmacological activator (RO0281675) interacts with GCK at this site. V62M GCK does not respond to RO0281675, nor does it respond to the hepatic glucokinase regulatory protein (GKRP). The enzyme is also thermally unstable, but this lability is apparently less pronounced than in the proven instability mutant E300K. Functional and structural analysis of seven amino acid substitutions at residue Val62 has identified a non-linear relationship between activation by the pharmacological activator and the van der Waals interactions energies. Smaller energies allow a hydrophobic interaction between the activator and glucokinase, whereas larger energies prohibit the ligand from fitting into the binding pocket. We conclude that V62M may cause hyperglycemia by a complex defect of GCK regulation involving instability in combination with loss of control by a putative endogenous activator and/or GKRP. This study illustrates that mutations that cause hyperglycemia are not necessarily kinetically inactivating but may exert their effects by other complex mechanisms. Elucidating such mechanisms leads to a deeper understanding of the GCK glucose sensor and the biochemistry of beta-cells and hepatocytes.